The features of real nutrition of preschool children in conditions of industrially polluted territories - Antonova, O. V. (Journal of Education, Health and Sport, 2018)
An integral part of industrialized areas is the constant increase of technogenic influence on the human body. This contributes to the deterioration of health of the population and, above all, of children as the most sensitive contingent. The industrial district of the Dnipro city, which is characterized by intense pollution of the environment, is selected for research. It should be emphasized that the residential area is located near the territory of the sanitary-protected zone of manufacturing enterprises. The particular attention was paid to selection of the control area. Since it is practically impossible to find an area that is homogeneous by parameters, but not technogenically polluted in an industrial city - the conventionally "pure" rural area, located in the recreation area, has been chosen as a control one. The purpose of the work was to give a hygienic assessment of the actual nutrition of children living in an industrially contaminated area, compared with the actual nutrition of kids in areas where there are no powerful industrial enterprises, in order to determine the compliance of food with current norms of physical needs of this contingent. Assessment of nutrition of children of preschool age was carried out in kindergartens using 10-day menu-schedules, the analysis of which indicates their non-compliance with hygiene requirements. The received data testifies that the actual daily nutrition in kindergartens is scarce primarily with the number of biologically important products for the growing organism of the child: of animal origin - meat, fish up to 50%, dairy products from 25-26% to 85%, as well depleted amount of fruits and vegetables as sources of vitamins, trace elements and food fibers up to 71% with excessive consumption of cereals, pasta, sugar and sweets. It should be added that the actual nutrition of children in the industrial region is imperfect and unbalanced by all major macro- and micro-nutrients with the insufficiency of the proteins, which in turn enhances the toxic effects of anthropogenic pollutants, reduces the organism’s response to adverse environmental factors, potentiates the risk of health problems and causes the need to adjust their nutrition. Thus, the obtained results show the necessity of continuing the comprehensive hygienic researches in this direction and are the scientific basis for studying the food supplement of the population, including children, as the most vulnerable part of the population to environmental factors, of other industrialized regions of the Dnipro and other powerful industrial regions as well as are the scientific basis for the search and implementation of effective remedies for its correction.